Antimicrobial Stewarding with a Unique Pharmacist-Managed Penicillin Skin Testing (PST) Service. (4th October 2017) - Wrenn, Rebekah; Sarubbi, Christina; Kleris, Renee; Drew, Richard; Moehring, Rebekah; Lugar, Patricia; Anderson, Deverick
Abstract: Background: Penicillin allergy has emerged as a key focus area for antimicrobial stewardship programs (ASP) due to the negative consequences this label can have on patient care. PST is a tool to determine allergy status and thus improve care by optimizing effective antimicrobial therapy in patients who are not likely to be allergic. Novel strategies for implementation of PST are needed as time, expertise, and follow-up are required to successfully implement a PST program. Methods: We performed this prospective observational study of the implementation of a unique ASP pharmacist-led PST consult service. Eligible inpatients were identified through prospective audit, pharmacy-led allergy assessments, and consultation from providers. PST training was completed through collaboration with allergy staff. Two ASP pharmacists and 1 allergy fellow performed testing on qualifying inpatients. Data were collected on the specifics of allergy history, PST results, antibiotic indication, and antibiotics received before and after testing. Results: A total of 1540 unique patients admitted at Duke University Hospital from 11/1/17 to 3/31/17 were labeled as "allergic to penicillin" on admission. Allergy assessments were completed on 107 patients. A total of 49 PST consults were performed and 23 of these patients (47%) underwent PST. Progress notes and allergy flags were updated on all PST patients. PST was negative for 21 (91%) patients; of these, 16 (76%) had their current antimicrobial therapy discontinued or de-escalated.-resistant pathogens or appropriate empiric coverage limited de-escalation in all 5 patients continued on broad coverage during study admission. One patient tested positive and one had an equivocal PST. No adverse effects related to PST or antimicrobials received following PST were observed. Allergy colleagues aided PST decision-making as needed. Conclusion: Stewardship pharmacist-led PST service is a unique approach that led to the removal of penicillin allergies for 91% of patients tested and to the safe use of β-lactam therapy at an academic medical center. This is a feasible and an effective additional ASP activity, particularly in settings where allergy consultation is not available. Disclosures: All authors: No reported disclosures.